Socratic Questioning 2.0 to Stimulate Deep Learning in English Class - Febrianingrum, Lasmi; Munir, Ahmad (Tell : Teaching of English Language and Literature Journal, 2025)
Socratic questioning, rooted in classical philosophy, remains a cornerstone of critical thinking and reflective learning. However, its traditional application requires adaptation to align with the demands of 21st-century education, which prioritizes technology integration, collaboration, and real-world relevance. This article introduces Socratic Questioning 2.0, a reimagined framework that merges classical inquiry techniques with digital tools and student-centered methodologies. By fostering deep learning, this modern approach enhances students' critical thinking, creativity, and engagement. The study explores the theoretical foundation of Socratic questioning, identifies its limitations in modern contexts, and proposes practical innovations to address these challenges. Key characteristics, such as the integration of digital platforms, contextualized questioning, and collaborative engagement, are highlighted alongside implementation procedures that include teacher training and adaptive technologies. Empirical evidence supports the effectiveness of this approach in developing critical skills essential for lifelong learning. By redefining Socratic questioning, this framework equips educators and learners to navigate the complexities of contemporary education. This study particularly examines the implementation of Socratic Questioning 2.0 in English language teaching contexts, where traditional methods often fall short in developing critical thinking and language proficiency simultaneously. The research demonstrates how this modernized approach effectively addresses the unique challenges of language acquisition while fostering deeper learning outcomes.